Religionshistorien og "De Andre" - Jensen, Jeppe Sinding (Religionsvidenskabeligt Tidsskrift, 1988)
The History of Religions as an academic enterprise has traditionally been concerned with the study of Otherness, i.e. non-Christian traditions. This article focuses on the ways in which historians of religions have constructed Other religions in accordance with Western and Christian theologically inspired concepts of religion. Such constructions of religious Otherness have mainly been based on universalist and nostalgic views of religion, without regard to the historicity of scholarly work. The History of Religions is basically a comparative enterprise, illustrated here by the ideas of Clifford Geertz, by the emic/etic distinction and in a discussion of the three main frames of comparison: relativism, evolutionism and universalism, all of which may often be found in any single treatment of Other religions.